Multi-Pharmaceutical Activities of Chinese Herbal Polysaccharides in the Treatment of Pulmonary Fibrosis: Concept and Future Prospects - Wu, Xianbo; Huang, Jianli; Wang, Jie; Xu, Yihua; Yang, Xinwei; Sun, Minghan; Shi, Jianyou (Frontiers in Pharmacology, 2021)
Pulmonary fibrosis is a fatal chronic progressive respiratory disease, characterized by continuous scarring of the lung parenchyma, leading to respiratory failure and death. The incidence of PF has increased over time. There are drugs, yet, there are some limitations. Hence, it is of importance to find new therapies and new drugs to replace the treatment of pulmonary fibrosis. In recent years, there have been a great number of research reports on the treatment of traditional Chinese medicine polysaccharides in various system fields. Among them, the treatment of PF has also gained extensive attention. This review summarized the source of polysaccharides, the drug activity of traditional Chinese medicine, and the protective effects on targets of PF. We hope it can inspire researchers to design and develop polysaccharides, serving as a reference for potential clinical therapeutic drugs.